2019
DOI: 10.1186/s13104-019-4411-0
|View full text |Cite
|
Sign up to set email alerts
|

The pluripotency transcription factor Nanog represses glutathione reductase gene expression in mouse embryonic stem cells

Abstract: Objective Redox homeostasis maintenance is essential to bring about cellular functions. Particularly, embryonic stem cells (ESCs) have high fidelity mechanisms for DNA repair, high activity of different antioxidant enzymes and low levels of oxidative stress. Although the expression and activity of antioxidant enzymes are reduced throughout the differentiation, the knowledge about the transcriptional regulation of genes involved in defense against oxidative stress is yet restricted. Since glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…2D and E. The efficacy of each shRNA showed a significant reduction in the expression of each of the TFs evaluated compared to the shGFP (Additional file 1: Figure S5), similar to our previous works [51][52][53][54][55][56][57]. Surprisingly, none of the shRNA targeting Oct4, Sox2 or Nanog, modified the previously reported response of the Nanog promoter to AKT compared to the control shRNA (Fig.…”
Section: Akt1 Induces Nanog In a Sumoylation Dependent Manner In Plur...supporting
confidence: 87%
“…2D and E. The efficacy of each shRNA showed a significant reduction in the expression of each of the TFs evaluated compared to the shGFP (Additional file 1: Figure S5), similar to our previous works [51][52][53][54][55][56][57]. Surprisingly, none of the shRNA targeting Oct4, Sox2 or Nanog, modified the previously reported response of the Nanog promoter to AKT compared to the control shRNA (Fig.…”
Section: Akt1 Induces Nanog In a Sumoylation Dependent Manner In Plur...supporting
confidence: 87%
“…2A). All shRNA encoding vectors have been previously used [28][29][30]38,39,41] and were highly effective in silencing the respective TF (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between pluripotency TFs and the components of the oxidative stress defense systems remains poorly explored. We have previously found that OCT4, SOX2, and NANOG regulate the expression of Sod1, Sod2, and Gsr [28–30], revealing a regulatory link between pluripotency TFs and the antioxidant system. In this work, we found that the pluripotency TF OCT4 represses the Hmox1 gene, demonstrating a meaningful connection between the pluripotency core and this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH, in turn, can be regenerated from its oxidized disulfide form (GSSG) by glutathione reductase (GR) using reduced nicotinamide adenine dinucleotide phosphate (NADPH) as an electron donor. In PSCs glutathione reductase is increased throughout ESC differentiation [ 142 ]. However, it is not clear whether the increase in GR expression precedes differentiation initiation, or whether GR activation is a byproduct of the switch to OxPhos.…”
Section: Prevention Of Oxidative Damagementioning
confidence: 99%